Perché Indra beve il soma in tanti modi diversi? Uno studio sui composti sinonimici del R̥gveda e sull’interazione fra poesia e grammatica (Atti del Sodalizio Glottologico Milanese, 2017)
The presence of many synonimical derivatives from the Vedic root pā- “drink” is thoroughly examined according to their compositional, metrical and stylistic features. KEYWORDS: Vedic, soma, drink, compounds, synonyms,